The electric vehicle conversion handbook : how to convert cars, trucks, motorcycles, and bicycles : includes EV components, kits, and project vehicles - Warner, Mark (HP books, 2011)
This is a book that describes how to convert an internal combustion-powered car or truck into and electric vehicle (EV). At first glance, this may seem like a daunting task for someone new to the world of EVs, but rest assured that converting a car to electric power isn't nearly as difficult as it may seem? -Introductioin, p. v.